Overcoming high power limitation of thin film resistors at GHz frequencies using CVD diamond substrates (2017)
We show RF resistors able to operate above 8 GHz while handing >100 W can be obtained by switching the resistor substrate to CVD diamond. Obtaining high power resistors able to operate above S-Band requires reducing its parasitic electrical characteristics to a minimum. In this work we demonstrate that this cannot be achieved with traditional substrates (AlN and BeO), but it is straightforward when using CVD diamond. This is clearly illustrated through the resistor's parameter 'capacitance per watt'. We also compare the performance of the different substrates for high power resistors using a model of a 75 W Wilkinson divider operating at 10 GHz.